A Preliminary Study of Yeast Strain Influence on Chemical and Sensory Characteristics of Apple Cider - Madeleine L. Way; Joanna E. Jones; Rocco Longo; Robert G. Dambergs; Nigel D. Swarts (Fermentation, 2022)
During the fermentation of apple juice, yeast metabolism creates complex biosynthetic pathways which produce a range of compounds responsible for the organoleptic qualities of cider. In this study, basic cider quality parameters were measured to investigate the influence of six yeast strains on cider made from three apple varieties (‘Pink Lady’, ‘Sturmer’, and ‘Bulmer’s Norman’). Measurement of pH, titratable acidity, and total phenolic content revealed that yeast can influence cider attributes, albeit variety and season dependent. Descriptive sensory analysis using a trained sensory panel was conducted on cider made from ‘Pink Lady’ apples and the same six yeast strains. The sensory panel significantly differentiated the yeast strains on the attributes of ‘fresh apple’, ‘earthy’ and ‘pear’. Identifying the variety specific influence of individual yeast strains on chemical and sensory characteristics of apple cider will provide cider makers with an enhanced understanding when choosing yeast strains.